Inhibition of planktonic growth and biofilm formation of Staphylococcus aureus by entrectinib through disrupting the cell membrane - Liu, Shanghong; Xiong, Yanpeng; Xiao, Haitao; Zheng, Jinxin; Wen, Zewen; Li, Duoyun; Deng, Qiwen; Yu, Zhijian (Frontiers in Microbiology, 2023)
Over the last few decades, Staphylococcus aureus infection has remained a major medical challenge and health concern worldwide. Biofilm formation and antibiotic resistance caused by S. aureus make it difficult to be eradicated bacterial infections in clinics. In this study, our data demonstrated the antibacterial and excellent anti-biofilm activity of entrectinib against S. aureus. Entrectinib exhibited good safety, suggesting no toxicity with the antibacterial concentration of entrectinib toward the erythrocytes and mammalian 239T cells. Moreover, entrectinib significantly reduced the bacterial burden of septic tissue in a murine model of MRSA infection. Global proteomic analysis of S. aureus treated with entrectinib showed significant changes in the expression levels of ribosomal structure-related (rpmC, rpmD, rplX, and rpsT) and oxidative stress-related proteins (Thioredoxin system), suggesting the possible inhibition of bacterial protein biosynthesis. Moreover, the increased production of reactive oxygen species (ROS) in entrectinib-treated S. aureus also supported the expression changes of ROS-correlated proteins involved in oxidative stress. Furthermore, entrectinib-induced resistant S. aureus clone was selected by induced in vitro under entrectinib exposure, and 3 amino acid mutations in the entrectinib-induced resistant S. aureus strain, 2 of which were located in the gene encoding Type II NADH: quinone oxidoreductase and one were found in GTP pyrophosphokinase family protein. Finally, the bactericidal action of entrectinib on S. aureus was confirmed by disrupting the bacterial cell membrane. Conclusively, entrectinib exhibit the antibacterial and anti-biofilm activity by destroying cell membrane against S. aureus.